ESG Scores’ Impact on Portfolio Performance, An Evidence from Indonesia - Kusno, John Iwan; Hartanto, Fransisca Tharia; Trilaksono, Teddy (Universitas Prasetiya Mulya, 2024)
This study is to determine the effect of using the Refinitiv ESG score in stock picking and its impact on portfolio performance using the ESG Score. Methodology for this research using a two-sample t-test of Net Asset Value (NAV) price-return portfolios and the Sharpe ratio as a proxy for risk adjustment return for portfolio evaluation. The results of this study indicate that the use of a Refinitiv rating may serve as a suitable metric for stock selection strategy because companies with higher ESG scores tend to exhibit superior performance. Since ESG ratings in Indonesia are still difficult to obtain, those with access to ESG ratings will have more advantages. Greater return performance is followed by an increased level of risk. Given the assumption of a well-diversified portfolio, it is hypothesized that the increased risk can be attributed to a larger variance coefficient. So that the Sharpe ratio must be used for portfolio evaluation to measure risk-adjusted returns.